2012
DOI: 10.1111/bjh.12024
|View full text |Cite
|
Sign up to set email alerts
|

High one year mortality in adults with sickle cell disease and end‐stage renal disease

Abstract: SummaryAdequate pre-dialysis care reduces mortality among end-stage renal disease (ESRD) patients. We tested the hypothesis that individuals with ESRD due to sickle cell disease (SCD-ESRD) receiving pre-ESRD care have lower mortality compared to individuals without pre-ESRD care. We examined the association between mortality and pre-ESRD care in incident SCD-ESRD patients who started haemodialysis between 1 June, 2005 and 31 May, 2009 using data provided by the Centers for Medicare and Medicaid Services (CMS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 14 publications
2
100
1
Order By: Relevance
“…And most of our patients (61%) had at least 3 severe SCD-related complications and comorbidities at baseline. In fact, some of our patients had a predicted survival of #60% within 4 years, 24,54,55 which approximates the 5-year survival rate for patients diagnosed with leukemia (59.7%), non-Hodgkin lymphoma (70.7%), and colon and rectum cancer (65.1%) between 2006 and 2012 based on data from Surveillance, Epidemiology, and End Results (SEER) (http://seer.cancer.gov). Risks that might be unique to haploidentical HSCT for SCD were not well known at the time this trial opened in 2009, so patients with significant sickle cell-related morbidity were enrolled when the potential benefits of a transplant outweighed potentially higher risks, and an enrollment age of 18 years was chosen so that all patients could provide consent for themselves.…”
Section: Discussionmentioning
confidence: 76%
“…And most of our patients (61%) had at least 3 severe SCD-related complications and comorbidities at baseline. In fact, some of our patients had a predicted survival of #60% within 4 years, 24,54,55 which approximates the 5-year survival rate for patients diagnosed with leukemia (59.7%), non-Hodgkin lymphoma (70.7%), and colon and rectum cancer (65.1%) between 2006 and 2012 based on data from Surveillance, Epidemiology, and End Results (SEER) (http://seer.cancer.gov). Risks that might be unique to haploidentical HSCT for SCD were not well known at the time this trial opened in 2009, so patients with significant sickle cell-related morbidity were enrolled when the potential benefits of a transplant outweighed potentially higher risks, and an enrollment age of 18 years was chosen so that all patients could provide consent for themselves.…”
Section: Discussionmentioning
confidence: 76%
“…In a large prospective study of 725 individuals with SCD, the median age at diagnosis of ESRD was 23.1 years for individuals with SCA, and median age at time of death was 27 years [109]. While, renal replacement therapy with hemodialysis can extend survival, the start of dialysis is a poor prognostic factor with 1-year mortality of 26% [14,110]. Glomerular hypertension and hyper-filtration are characteristic of early sickle cell glomerulopathy, and albuminuria is its earliest clinical correlate [111][112][113].…”
Section: Pulmonary Complicationsmentioning
confidence: 99%
“…44 More recently, it was reported that although patients with SCD are at high risk of dying within the first year of starting dialysis, the mortality rate in this group was significantly lower in those who received predialysis nephrology care compared with those who did not. 45 In our practice, we have success with both hemodialysis and peritoneal dialysis in patients with ESRD secondary to SCN. Hemodialysis offers the advantage of ease of access for blood transfusion, whereas peritoneal dialysis is often preferable for those who have run out of options for permanent venous access.…”
Section: Renal Replacement Therapymentioning
confidence: 99%